جماليات تحوُّل الوحدة الصرفيَّة لدى النُّحاة والبلاغيين (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
يتناول هذا البحث جماليات تحوُّل الوحدة الصرفيَّة لدى النُّحاة والبلاغيين. يبدأ البحث بتناول مفهوم التحوُّل الصَّرفي في توليد الألفاظ وتنمية الثروة اللفظية، ورصد مظاهر التحوُّل عن الأصل، والتغيرات التي تحدث في بنية الكلمة تنقلها من الأصل المجرَّد إلى الأصل المستعمل... يحاول البحث الوقوف على رصد أغراض تحوُّل الوحدة الصرفيَّة الدَّلالية والجمالية التي تتمثَّل في تقوية المعنى باستخدام صيغ تدلُّ على التكثير والمبالغة أوِ القوَّة بدل صيغة أخرى، كما يحاول تبيين أنواع الوحدة الصرفيَّة، الحرَّة والمقيَّدة، وتبيين أنَّ الوحدة الصرفيَّة هي إشارات أو علامات تسبح في فضاء الخطاب دون قيد دلاليّ أو بنيويّ، ودلالاتها متولِّدة من حريَّة تخلُّصها من السَّوابق واللواحق  التي يوظِّفها المبدع لتحقيق غايته الفنيَّة والجمالية والفكرية، وكذلك المقيَّدة إمّا بسوابق تأتي في رصد الكلمة، وإمَّا بلواحق تكون في آخر الكلمة مرتبطة بالجذر لا تفارقه، ودلالاتها لا تُكتسب إلاّ من خلال الارتباط به، وينتهي البحث بالحديث عن سرِّ الجمال الفنِّي للتحوُّل ودوره في التفريق بين معاني الوحدات الصرفيَّة ودلالاتها. This paper deals with the syntactic and rhetoric aesthetics of morpheme transformation. We start by examining the concept of morphological transformation in generating words and enriching vocabulary, keeping track of the characteristics of derivation from the original form; the changes that occur to word structure transform it from the abstract original form to the original form in use. This paper attempts to focus on the purposes of the semantic and aesthetic transformation of the morpheme for enhancing meaning by using forms expressing abundance and exaggeration. In so doing, this paper shows the types of morpheme, be they free of hound, making it clear that a morpheme is a bundle of features used in discourse without any semantic or structural constraints; its semanticity is brought about by being free of prefixes and suffixes used by a scholar for intellectual, aesthetic, and artistic ends. For example, bound morphemes are either semanticity of which can't be retrieved but being attached to it. We conclude this paper by considering the secret artistic beauty of this transformation and its role in distinguishing between the meanings of morphemes and what they refer to.